1981
DOI: 10.1111/j.1699-0463.1981.tb00218.x
|View full text |Cite
|
Sign up to set email alerts
|

Metastases to the Breast From Extramammary Carcinomas

Abstract: Metastases to the breast from extramammary carcinomas. Acta path. microbiol. scand. Sect. A, 89: 251-256, 1981. Metastases to the breast from extramammary carcinomas are rare. Only about 200 cases are reported in the literature. Fifteen additional cases are presented here and the literature is reviewed. Two of the patients had primary thyroid carcinoma, two adenocarcinoma of the colon, three bronchogenic carcinoma, four malignant melanoma, one a squamous cell carcinoma of the oesophagus, one an adenocarcino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
2

Year Published

1998
1998
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 23 publications
(10 reference statements)
0
35
0
2
Order By: Relevance
“…Twelve of these cases were classified as adenocarcinomas (5,9,12,19,(21)(22)(23)25). Additionally, 53 cases of breast metastasis from lung tumors were presented; however, no detailed histological classification was provided (7,18,(28)(29)(30). The majority of breast metastases present as palpable, rapidly growing, well-circumscribed and painless breast masses with predilection to the upper outer quadrant (2,7,17,21,22).…”
Section: Histopathological and Immunohistochemical Findingsmentioning
confidence: 99%
“…Twelve of these cases were classified as adenocarcinomas (5,9,12,19,(21)(22)(23)25). Additionally, 53 cases of breast metastasis from lung tumors were presented; however, no detailed histological classification was provided (7,18,(28)(29)(30). The majority of breast metastases present as palpable, rapidly growing, well-circumscribed and painless breast masses with predilection to the upper outer quadrant (2,7,17,21,22).…”
Section: Histopathological and Immunohistochemical Findingsmentioning
confidence: 99%
“…The fact that such cases are rare in males supports this theory, particularly as most of these tumors tend to be metastases from prostatic carcinomas in patients treated with estrogens, which are known to increase the mammary blood fl ow. [14][15][16] Synovial sarcoma originates in the deep soft tissues and primarily appears in close proximity to limb joints. The tumor accounts for 5.6%-10.0% of all soft tissue tumors, and 72% of the patients are younger than 40 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…Malignant melanoma, lymphoma, lung cancer, ovarian carcinoma, soft tissue sarcoma are the most common cancers to metastasize to breast (8,13,14). Metastases from osteosarcoma, gastric cancer, cervical, vaginal and endometrial carcinomas to the breast were also reported sporadically in the literature (8,(13)(14)(15). To our knowledge this is the fifth case of thyroid cancer and second case of follicular sub-type reported metastasizing to the breast (3-6).…”
Section: Discussionmentioning
confidence: 89%